Role of antioxidant defence, renal toxicity markers and inflammatory cascade in disease progression of acute pyelonephritis in experimental rat model. (August 2017) - Vysakh, A.; Raji, Nair R.; Suma, D.; Jayesh, Kuriakose; Jyothis, Mathew; Latha, M.S.
Abstract: Urinary tract infections are the most common bacterial infections affecting millions of people each year worldwide. The animal model provides an excellent and suitable system for studying cystitis and pyelonephritis caused by Escherichia coli and other uropathogens. Using this established model, we evaluate the role of antioxidant defence system, renal injury markers, and blood parameters in the diseases progression during Escherichia coli infection on 0 th day, 12h and 7 th day. The antioxidant enzymes like SOD, CAT, GSH, GPx, GR levels were evaluated. The blood parameters like AST, ALT, ALP, Total protein, BUN, creatinine level were estimated in infection model. The relative organ weights, anti microbial status of kidney, CRP, WBC count were done for the evaluation of inflammatory response associated with the infection. The oxidative stress marker like MDA was also evaluated. Histopathological analysis of renal tissue provides direct vision to tissue damage. The antioxidant status of renal tissue was decreased during the 7 th day of infection. Likewise, renal toxicity markers were significantly increased during bacterial infection. The inflammatory markers like CRP, WBC count and oxidative stress marker like MDA were significantly increased by the infection on 7 th day. The histopathology of renal tissue also reveals the inflammation and tissue damage associated with acute pyelonephritis. Highlights: Role of antioxidant defence and inflammatory cascade in disease progression of acute pyelonephritis was studied in experimental rat model. The animals were infected with clinically isolated E-coli for evaluating the progression of infection. The antioxidant enzymes, blood parameters, oxidative stress markers and anti microbial status of kidney were evaluated. The inflammatory markers and oxidative stress marker were significantly increased by the infection on 7 th day.